Lonicerae Japonicae Flos extract and chlorogenic acid attenuates high-fat-diet- induced prediabetes via CTRPs-AdipoRs-AMPK/PPARα axes - Guo, Chengcheng; Zhang, Xiaoyuan; Yu, Yingxiang; Wu, Yifan; Xie, Lan; Chang, Cuiqing (Frontiers in Nutrition, 2022)
Prediabetes is considered an important reversible checkpoint in T2DM development, which can be delayed and prevented by early interventions. Lonicerae Japonicae Flos (LJF), an edible-medicinal herb, is rich in chlorogenic acid (CGA, 5-O-caffeoylquinic acid) and exerts anti-diabetes effects, but its role in prediabetes remains unclear. The purpose of this study was to explore the effects of LJF extract and CGA on rat with prediabetes. Sprague-Dawley rats were given high-fat diet (HFD) to induce prediabetes, and glycolipid metabolism parameters and molecular mechanisms were evaluated. LJF (the LJF extract treatment group) and CGA (the pure CGA treatment group) significantly attenuated HFD-induced prediabetes with impaired glucose tolerance and dyslipidemia, but their mechanisms of action are not exactly the same. Specifically, LJF prioritizes increasing protective lipid species (such as increasing blood polyunsaturated fatty acids (PUFA)-containing diacylglycerol (DAG) species, high-density lipoprotein-cholesterol (HDL-C)), whereas CGA prioritizes reducing detrimental lipid species (such as saturated fatty acid-containing DAG species, low-density lipoprotein-cholesterol (LDL-C), total cholesterol (TC)). In addition, CGA significantly increased the content of blood very-long-chain fatty-acid (VLCFA)-containing ceramides species. This could be explained mechanically by a distinction between LJF and CGA's effects on C1q/TNF-related proteins (CTRPs) which activate adiponectin receptors, triggering several downstream reactions. Because both LJF and CGA upregulated liver expression of adiponectin receptors (AdipoR1 and AdipoR2) and enhanced the activity of downstream AMPK. LJF also increased serum levels of CTRP3 and CTRP9, especially CTRP9, whereas CGA had higher serum CTRP3 and upregulated liver PPARa expression. Additionally, ELOVL6 expression in the liver was greater in CGA than LJF. This study demonstrates that LJF and CGA exert hypoglycemic and lipid modulation capacity to prevent prediabetes may through the CTRPs-AdipoRs-AMPK/PPARα axes and promoting ELOVL6 protein expression.